2022
DOI: 10.3389/fonc.2022.837930
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Ganglioside GM1 From Breast Tumor Cells Stimulated Epithelial-to-Mesenchymal Transition of Recipient MCF-10A Cells

Abstract: Small extracellular vesicles (sEVs) are a type of membrane structure secreted by cells, which are involved in physiological and pathological processes by participating in intercellular communication. Glycosphingolipids (GSLs) are enriched in sEV and can be delivered to recipient cells. In this study, we found that overexpression of B3GALT4, the glycosyltransferase responsible for ganglioside GM1 synthesis, can induce the epithelial–mesenchymal transition (EMT) process in MCF-10A cells. Moreover, GM1 was verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Subsequent investigation revealed that these GM1-enriched EVs from cancer cells transferred their ganglioside components to recipient cells, promoting epithelial-mesenchymal transition (EMT) properties. This further upregulated mesenchymal-related genes such as vimentin and N-cadherins while downregulating the expression of E-cadherin, providing further insight into the molecular mechanism of EMT induction mediated by these GM1-enriched EVs in normal recipient cells ( Ma et al, 2022 ). This suggests a novel and crucial regulatory role of EV associated gangliosides that orchestrates the cellular communication in different pathophysiological circumstances.…”
Section: Effect On Invasion and Migrationmentioning
confidence: 96%
“…Subsequent investigation revealed that these GM1-enriched EVs from cancer cells transferred their ganglioside components to recipient cells, promoting epithelial-mesenchymal transition (EMT) properties. This further upregulated mesenchymal-related genes such as vimentin and N-cadherins while downregulating the expression of E-cadherin, providing further insight into the molecular mechanism of EMT induction mediated by these GM1-enriched EVs in normal recipient cells ( Ma et al, 2022 ). This suggests a novel and crucial regulatory role of EV associated gangliosides that orchestrates the cellular communication in different pathophysiological circumstances.…”
Section: Effect On Invasion and Migrationmentioning
confidence: 96%